Hydrodynamic modelling of microplastics transport in Bach Dang estuary - Le, Duc Cuong; Duong, Thanh Nghi; Duong, Thi Lim; Nguyen, Quoc Trinh; Nguyen, Van Thao; Dao, Dinh Cham; Nguyen, Ba Thuy; Du, Van Toan (Vietnam Journal of Marine Science and Technology, 2022)
In this study, the three-dimensional Delft3D-PART model was applied to study micro-plastics transport in the Bach Dang estuary. Micro-plastics as data input for the model in this study were assessed by taking water samples by 80 μm mesh size plankton net, and sediment samples by Petersen grab. The determination of input parameters for the micro-plastic transport model through averaging the particle characteristics of micro-plastics has been applied. Microplastics results appear in 10 water samples and 10 sediment samples surveyed. The results of micro-plastics in the water body of Bach Dang estuary presented that the regional tidal regime was closely related to the number of micro-plastics according to the season. In the wet season, the number of micro-plastics was around 2–3 nr/m3, spreading stronger than in the dry season.